Effects of carbon-to-nitrogen ratios and nitrogen sources on composting of mushroom residue - BAI Yongjuan; XU Weinan; CHANG Xiaoxiao; HU Xiaohui (浙江大学学报. 农业与生命科学版)
With the increase production of agricultural products by years, large quantitative accumulations of agricultural waste have brought severe environmental problems and wasting of resources. Therefore, recycling and reusing the agricultural waste become urgent. Recently, composting of agricultural waste has become the research focus of soilless culture substrate. With the advantages such as stable physiochemical property, adequate supply of fat, wide variety of sources and low cost, soilless culture substrates have been accepted by majority of farmers, and the demand for substrates increased quickly. Mushroom waste contains large amounts of mycoprotein, a variety of metabolites and underutilized nutrients, which is a good substrate material. In this study, mushroom residue was selected as the main material for composting, the effects of different carbon-to-nitrogen ratios and nitrogen sources on physiochemical properties of composting were investigated, to find the optimal condition for transformation of mushroom residue to soilless culture substrate, to provide optimized composting parameters for the practical production, to offer scientific basis for the widespread application of the mushroom substrates.The carbon-to-nitrogen (C/N) ratio was set at three levels of 25∶1, 30∶1, and 35∶1. Five different combinations of nitrogen sources were selected, including cow manure, chicken manure, urea, a mixture of cow manure and urea, and a mixture of chicken manure and urea. Actually, the C/N ratio of mushroom was 40∶1, and the dry cow manure, dry chicken manure and urea were used to adjust the C/N ratio. Each treatment contained 100 kg mushroom residue and 3% effective microorganism (EM) agents, and the water content was adjusted to 60%. Static composting at high temperature was applied and the experimental containers were covered by plastic sheeting. The piles were turned over every 10 days, and were sampled every 15 days for a study period of 80 days. Composting temperature, total porosity, air-filled porosity, water holding capacity, air-water ratio, electrical conductivity (EC), pH and bulk density were measured for each sample. The temperature in center of each pile was recorded using a temperature meter every day.The results showed that during the composting period, the C/N ratios had significant influence on all parameters, while the nitrogen sources had significant influence on all parameters except total porosity. The optimal condition to keep high temperature (>50 ℃, and last for 8, 8 and 9 days, respectively), and to shorten the composting period of mushroom residue was C/N ratio of 30∶1, and adding the mixture of cow manure or chicken manure and urea as an additive nitrogen source. Under the C/N ratio of 30∶1, bulk density and porosity tend to be stable after 70-day fermentation, beneficial to composting of mushroom residue. When the mixture of cow manure or chicken manure and urea was added as nitrogen source, bulk density, water holding capacity, pH and EC values tended to be stable after 70-day composting.In conclusion, the optimal condition for composting of mushroom residue is the initial C/N ratio of 30∶1 and the mixture of cow manure or chicken manure and urea as the nitrogen source.